Effects of dietary supplementation with increasing doses of lactose on faecal bacterial populations and metabolites and apparent total tract digestibility in adult dogs. Issue 4 (2nd October 2018) - Grandi, Monica; Pinna, Carlo; Bonaldo, Alessio; Stefanelli, Claudio; Vecchiato, Carla Giuditta; Zaghini, Giuliano; Biagi, Giacomo
Abstract: The effect of increasing dietary doses of lactose on canine faecal microbiota and apparent digestibility was evaluated. Fourteen adult healthy dogs [1–5 years of age, mean body weight (BW) of 19.0 kg] were fed with an extruded diet containing silica (5 g/kg) as a digestion marker. After a 20 d adaptation period, increasing doses of lactose were added to the dogs' diet (0.5, 1 and 2 g/kg BW 0.75 /d) during three consecutive 20-d supplementation periods. Faeces were collected at the end of each period for analyses. Four dogs refused the diet added with lactose at 0.5 g/kg BW 0.75 /d and were excluded from the trial, as well as two dogs, which developed acute diarrhoea when lactose was fed at 1 g/kg BW 0.75 /d. Conversely, eight dogs remained healthy throughout the study. Faecal moisture was influenced by lactose (quadratic, p = .001), while faecal pH and ammonia were not affected by treatments. Lactose supplementations tended to linearly decrease isovalerate ( p = .051) and quadratically influence n -valerate ( p = .056) in canine faeces. No changes in faecal microbial populations were observed. Apparent digestibility of dry matter, Ca, K, Mn and Fe was influenced by lactose supplementation (quadratic, p < .05). Increasing doses of lactose linearly decreased Mg digestibility ( p < .05). Furthermore, coefficients of crude protein, crude ash, P, Mg and Zn digestibility were tendentially affected (quadratic, p = .055, .089, .091, .065 and .065, respectively). In conclusion, 8 of 14 dogs displayed a good tolerance (absence of gastrointestinal signs) up to the highest dose of lactose (2 g/kg BW 0.75 /d). An evident prebiotic effect was not observed.